Dietary effects of linseed on fatty acid composition of milk and on liver, adipose and mammary gland metabolism of periparturient dairy cows. Issue 1 (2nd May 2013) - Mach, N.; Zom, R. L. G.; Widjaja, H. C. A.; van Wikselaar, P. G.; Weurding, R. E.; Goselink, R. M. A.; van Baal, J.; Smits, M. A.; van Vuuren, A. M.
Summary: During the transition period in dairy cows, drastic adaptations within and between key tissues and cell types occur in a coordinated manner to support late gestation, the synthesis of large quantities of milk and metabolic homoeostasis. The start of lactation coincides with an increase of triacylglycerols in the liver, which has been associated with several economically important diseases in dairy cows (i.e. hepatic lipidiosis, mastitis). The polyunsaturated fatty acids have been used to improve liver metabolism and immune function in the mammary gland. Therefore, the effects of dietary linseed supplementation on milk quality and liver, adipose and mammary gland metabolism of periparturient dairy cows were studied in 14 cows that were randomly assigned to control or linseed supplementation. Animals were treated from 3 weeks antepartum until 6 weeks post‐partum. Linseed did not modify dry matter intake, but increased milk yield and lactose yield, and decreased milk fat concentration, which coincided with lower proportion of C16 and higher proportions of stearic acid, conjugated linoleic acid and α‐ linolenic acid in milk fat. Linseed supplementation did not significantly change the expression of key lipid metabolism genes in liver and adipose tissues, except of glucose transporter 2 ( GLUT2 ) in liver, which was increased in cows supplemented with linseed, suggesting that more glucose was secreted and probably available for lactose synthesis compared with cows fed control diet. Large adaptations of transcription occurred in the mammary gland when dairy cows were supplemented with linseed. The main affected functional modules were related to energy metabolism, cell proliferation and remodelling, as well as the immune system response.